Influence of Body Mass Index on Eating Habits and Food Choice Determinants Among Brazilian Women During the COVID-19 Pandemic - Mazzolani, Bruna Caruso; Smaira, Fabiana Infante; Esteves, Gabriel Perri; Santo André, Heloísa C.; Amarante, Milla Cordeiro; Castanho, Daniela; Campos, Karen; Benatti, Fabiana Braga; Pinto, Ana Jéssica; Roschel, Hamilton; Gualano, Bruno; Nicoletti, Carolina Ferreira (Frontiers in Nutrition, 2021)
Changes in emotional state due to the COVID-19 pandemic may potentially modify eating habits, which may differ as a function of body mass index (BMI). Using a self-reported, questionnaire-based survey we evaluated Brazilian women during the pandemic for: (i) the influence of BMI on changes in eating habits, food choice determinants, and psychological symptoms; (ii) associations between eating habits, food choice determinants and psychological symptoms. General characteristics, anthropometric data, eating habits before and during the pandemic, food choice determinants and psychological symptoms during the pandemic were collected between June and September, 2020. Participants (n = 1,183) were normal weight (60.4%), overweight (26.2%) and obese (13.4%). A higher frequency of “cooking” (72.3–77.6%, p = 0.004) and “use of delivery service” (29.8–48.8%, p < 0.001) was reported during, in comparison to before the pandemic. Additionally, a higher prevalence of “snacking” (57.1–63.8%, p = 0.005) and “eating at table” (78.5–82.7%, p < 0.001) was reported during the pandemic, while the number of participants reporting “dieting” decreased (28.7–20.4%, p < 0.001). “Health”, “natural concerns” and “need and hunger” were less important determinants for participants with overweight/obesity compared to normal weight. Regression analysis indicated that (i) “health”, “natural concerns” and “affect regulation”; (ii) “health”, “pleasure”, “convenience”, and “natural concerns”; and (iii) “visual appeal” and “pleasure” were the food choice determinants more associated with eating habits among women with normal weight, overweight, and obesity, respectively. In conclusion, eating habits were modified during the pandemic despite BMI, whereas food choice determinants differed between overweight/obesity and normal weight women.